On the obligations of states to respond to climate change and China’s legal consequences: based on the advisory opinion in case no. 31 of the international tribunal for the law of the sea - Zeng, Wanping; Wang, Guihua (Frontiers in Marine Science, 2025)
IntroductionClimate change presents a critical global challenge, requiring states to develop and implement robust legal and policy frameworks. The 2024 Advisory Opinion issued by the International Tribunal for the Law of the Sea (ITLOS) in Case No. 31 highlights the legal obligations of states under the United Nations Convention on the Law of the Sea (UNCLOS) to address climate change, emphasizing the role of the marine environment in this context.MethodsThis study conducts a comprehensive analysis of the Advisory Opinion and examines its implications for China’s existing climate change legal framework. The analysis identifies key challenges, including expanded legal responsibilities, the harmonization of international law with domestic legislation, and the increased risk of international climate litigation for domestic enterprises.ResultsThe Advisory Opinion establishes a higher standard for China’s legislative response to climate change, necessitating the integration of its international obligations into its domestic legal framework. Key findings reveal gaps in China’s current legal system and emphasize the need for proactive measures to align with international standards.DiscussionTo address these challenges, the paper proposes several recommendations: developing a comprehensive legal framework for climate change, reinforcing due diligence obligations, establishing a robust climate monitoring and assessment system, and enhancing the capacity of domestic enterprises to handle international climate litigation. These measures aim to position China as a proactive contributor to global climate governance.ConclusionThe study provides valuable insights for advancing China’s climate change law and aligning it with the international legal framework. The proposed measures serve as essential guidance for China to assume greater responsibility and influence within the global climate legal system.